OWN LAYER IN THE NOVEL "STARRY NIGHTS" BY PRIMQUL KADIROV - Rahimova Zarnigor Bahromovna (Academia Science Repository, 2023)
This article provides information about Primkul Kadyrov's work "Starry Nights" and the layer that flies in it. Opinions about one's own stratum are expressed and conclusions are drawn through excerpts from the work.